2014
DOI: 10.1007/s10142-014-0415-y
|View full text |Cite
|
Sign up to set email alerts
|

The MaASR gene as a crucial component in multiple drought stress response pathways in Arabidopsis

Abstract: Abscisic acid (ABA)-, stress-, and ripening-induced (ASR) proteins are involved in abiotic stress responses. However, the exact molecular mechanism underlying their function remains unclear. In this study, we report that MaASR expression was induced by drought stress and MaASR overexpression in Arabidopsis strongly enhanced drought stress tolerance. Physiological analyses indicated that transgenic lines had higher plant survival rates, seed germination rates, and leaf proline content and lower water loss rates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
19
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 52 publications
0
19
0
Order By: Relevance
“…Plant cells respond to dehydration through triggering several signal transduction pathways that result in accumulation of certain proteins, sugar molecules and lipophilic antioxidants ). Among the proteins, the ancestral ASR gene family served as an example of positive selection during colonization of arid regions by adaptive evolution following gene duplication (Zhang et al 2015). Varied expression of ASRs in response to stress-related signals and abiotic stresses Abscisic acid stress ripening transcripts accumulated under different abiotic stresses and ASR proteins acted as downstream components of a transduction pathway (Cakir et al 2003;Ricardi et al 2014;Zhang et al 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Plant cells respond to dehydration through triggering several signal transduction pathways that result in accumulation of certain proteins, sugar molecules and lipophilic antioxidants ). Among the proteins, the ancestral ASR gene family served as an example of positive selection during colonization of arid regions by adaptive evolution following gene duplication (Zhang et al 2015). Varied expression of ASRs in response to stress-related signals and abiotic stresses Abscisic acid stress ripening transcripts accumulated under different abiotic stresses and ASR proteins acted as downstream components of a transduction pathway (Cakir et al 2003;Ricardi et al 2014;Zhang et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Among the proteins, the ancestral ASR gene family served as an example of positive selection during colonization of arid regions by adaptive evolution following gene duplication (Zhang et al 2015). Varied expression of ASRs in response to stress-related signals and abiotic stresses Abscisic acid stress ripening transcripts accumulated under different abiotic stresses and ASR proteins acted as downstream components of a transduction pathway (Cakir et al 2003;Ricardi et al 2014;Zhang et al 2015). Systematic analyses of expression patterns showed that all six ASR genes in foxtail millet were induced by various abiotic stresses and stress-related signals (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…They are induced by water deficit and fruit ripening (Iusem et al, 1993). Since then, many ASR homologous proteins have been cloned from a variety of plants (Cakir et al, 2003; Kalifa et al, 2004; Virlouvet et al, 2011; Hu et al, 2013; Zhang et al, 2015). ASR gene families are widely distributed in monocots, dicots, herbs, and xylophyta, but no ASR ortholog have been identified in Arabidopsis (Wong et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…A wheat ASR gene, TaASR1 , increases drought and osmotic stress tolerance in transgenic tobacco by activating the antioxidant system and the expression levels of stress-responsive genes (Hu et al, 2013). Overexpression of banana ASR ( MaASR ) in Arabidopsis and rice ASRs ( OsASR1 and OsASR3 ) in rice has been shown to enhance drought and salt tolerance, respectively, in transgenic lines (Joo et al, 2013; Zhang et al, 2015). The loblolly pine ASR gene lp3 is induced by water deficit stress mediated by ABA (Padmanabhan et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Banana ( Musa acuminata ) is one of the most popular fresh fruits worldwide, and cultivated in the subtropical and tropical areas40414243. To date, many banana varieties have been screen and cultivated in China.…”
mentioning
confidence: 99%